2023
DOI: 10.3389/fpsyg.2023.1175934
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and resilience in children in mainland China: life satisfaction as a mediator

Abstract: IntroductionGrounded in the perspective of “Positive Youth Development” (PYD), resilience is an important developmental asset shaping human development. Although many studies have examined the impact of resilience on child developmental outcomes, relatively few studies have focused on the predictors of resilience, in particular familial antecedents of resilience in Chinese children and adolescents. In addition, the degree to which life satisfaction contributes to the mechanism by which family functioning impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In this study, we conducted a 3-wave longitudinal research on the psychosocial adjustment of Chinese preadolescents and adolescents with data gathered at three different time points: a baseline (Wave 1), six months later (Wave 2), and one and a half years later (Wave 3) from the baseline (e.g., Dou et al, 2023 ; Peng L.-L. et al, 2023 ). In 2020, there were 623 elementary schools, 317 junior secondary schools, and 156 schools admitting both elementary and junior secondary students in Chengdu.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we conducted a 3-wave longitudinal research on the psychosocial adjustment of Chinese preadolescents and adolescents with data gathered at three different time points: a baseline (Wave 1), six months later (Wave 2), and one and a half years later (Wave 3) from the baseline (e.g., Dou et al, 2023 ; Peng L.-L. et al, 2023 ). In 2020, there were 623 elementary schools, 317 junior secondary schools, and 156 schools admitting both elementary and junior secondary students in Chengdu.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding families, Dou et al (2023) observed the relationship between healthy family functioning and resilience in children and adolescents. Healthy family functioning depends on effective parenting, successful role functioning, and family cohesion to develop resilience (Dou et al, 2023;Masten, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding families, Dou et al (2023) observed the relationship between healthy family functioning and resilience in children and adolescents. Healthy family functioning depends on effective parenting, successful role functioning, and family cohesion to develop resilience (Dou et al, 2023;Masten, 2015). Baumrind divided parenting into three styles: authoritative, authoritarian, and permissive (Levin, 2011), with authoritative parenting being frequently associated with adolescent resilience (Baumrind et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial provision, family structure, socialization, safeguarding vulnerable family members, role fulfillment, emotional receptiveness, involvement, behavioral regulation, harmony, mutual support, and conflict resolution are also part of family functioning. The unique attributes of parent-child relationships, such as parental nurturing and authority, also indicate a family's functionality [81,82].…”
Section: The Direct Effect On Family Communication Family Functioning...mentioning
confidence: 99%